Deconstructing aesthetics of shadow puppet art in Wahyu Katentreman by Cahyo Kuntadi - Santoso, Eko Herry; Mibtadin, Mibtadin; Wibowo, Prasetyo Adi Wisnu (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
Abstract This study analyzes the aesthetic deconstruction in wayang kulit (shadow puppet) performances, focusing on the Wahyu Katentreman play performed by puppeteer Cahyo Kuntadi. The study aims to identify the causes, processes, and implications of aesthetic deconstruction in wayang kulit performances and their impact on the sustainability of this traditional art form in the modern era. Using Jacques Derrida’s deconstruction theory as the primary approach, this research also references Jakob Sumardjo’s paradoxical aesthetic theory and Sunardi’s concepts of nuksma and mungguh. A qualitative research method with an interpretative analysis technique was employed, utilizing both primary and secondary data sources. The findings indicate that aesthetic deconstruction in this wayang kulit performance is driven by changing audience preferences influenced by materialism and hedonism. The deconstruction process is evident in the transition from sacred to profane elements, the fusion of various performance styles from Surakarta, Yogyakarta, and East Java, as well as the integration of spontaneous humor within the Punakawan characters. The implications of this deconstruction include the emergence of new references for young puppeteers, increased appreciation of wayang kulit among the millennial generation, and economic benefits for karawitan music groups and local communities. Thus, this study asserts that aesthetic deconstruction in wayang kulit not only contributes to innovation in performing arts but also plays a crucial role in maintaining the relevance of traditional culture amidst dynamic social changes.